The restoration and opening of tomb of king ay, tomb of king Sipthain, tomb of king Siptah, tomb of king Rameses vii, tomb of Nefer-renpet, tomb of Nefer-sekhrw, tomb of Djehuty-mes = Termim ve iftitah-i mekabir-i el-melki ey, el-melki sibtah, el-melki ramsisil sabi, nefre renbet, nefri suhru, çehuti mis - Husni, Faruk (Luxor)
72 s.